The Importance of Early Treatment of Frontal Fibrosing Alopecia - Musbah , Fauzia; Lagha, Saja; Tabib, Mohmed (AlQalam Journal of Medical and Applied Sciences, 2024)
Frontal fibrosing alopecia (FFA) a variant of lichen planopilaris (LPP) described a gradual recession affecting the frontoparietal region in postmenopausal women, with the stark difference between the pale, smooth skin and the sun-damaged skin on the forehead, By trichoscopy, there’s a lack of hair follicle openings and the presence of perifollicular erythema at the hairline. With histopathological features include lymphocytic infiltration and fibrosing of the root sheet of hair follicle. We aimed to determine the relation between the duration of the disease and response to early initiation of different treatments. We conducted a retrospective study, including 16 cases of FFA from Tripoli Central Hospital, spanning from November 2019 to November 2023. In this study, we used data extracted from patients’ follow-up records, which included information on demographics, disease history, examination results, trichoscopy findings, and administered treatments. The process of data entry and analysis was conducted using SPSS 26. We found out of 16 participants which were all females, mean age of 53.50 (±4.94), history of duration in months was 54 (42-62). There was a statistically significant negative strong association between the response to the treatment and the duration of the disease, τb = -0.574, p-value = 0.011. الثعلبة الليفية الأمامية وهي أحد أشكال ثعلبة الحزاز المسطحة وصفت كتراجعًا تدريجيًا يؤثر على منطقه الجبهة لدى النساء بعد فترة انقطاع الطمث، مع وجود اختلاف بين الجلد الأملس والجلد التالف بسبب الشمس على الجبهة، من خلال منظار الشعر، هناك نقص في فتحات بصيلات الشعر ووجود احمرار حولها عند خط الشعر الأمامي. مع السمات المرضية التي تشمل التسلل الليمفاوي وتليف الطبقة الجذرية لبصيلات الشعر. هدفنا إلى تحديد العلاقة بين مدة المرض والاستجابة للبدء المبكر في علاجات مختلفة. أجرينا دراسة بأثر رجعي، شملت 16 حالة من الثعلبة الليفية الأمامية من مستشفى طرابلس المركزي، امتدت من نوفمبر 2019 إلى نوفمبر 2023. في هذه الدراسة، استخدمنا البيانات المستخرجة من سجلات متابعة المرضى، والتي تضمنت معلومات عن التركيبة السكانية وتاريخ المرض ونتائج الفحص ونتائج تنظير الشعر والعلاجات المقدمة. تم إجراء عملية إدخال البيانات وتحليلها باستخدام برنامج SPSS 26. وجدنا من بين 16 مشاركًا كانوا جميعًا من الإناث، متوسط أعمارهم 53.50 (±4.94)، وكان تاريخ المدة بالأشهر 54 (42-62). كان هناك ارتباط قوي سلبي ذو دلالة إحصائية بين الاستجابة للعلاج ومدة المرض، τb = -0.574، قيمة p = 0.011